EFFICACY OF INTENSE PULSED LIGHT THERAPY ON SIGNS AND SYMPTOMS OF DRY EYE DISEASE : A SYSTEMATIC REVIEW - Yovita, (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Introduction: Dry eye disease (DED) is a multifactorial disorder of the ocular surface characterized by disruption of tear film homeostasis, instability of the tear film, and inflammation of the ocular surface. Although the precise mechanism of action is still inadequately understood, numerous studies have demonstrated that IPL has the potential to alleviate both the signs and symptoms of dry eye.The aim: This article showed efficacy of intense pulsed light therapy on signs and symptoms of dry eye disease.Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2013 and 2023 were taken into account. Several different online reference sources, like Pubmed and SagePub, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done.Result: In the PubMed database, the results of our search brought up 112 articles, whereas the results of our search on SagePub brought up 109 articles. The results of the search conducted for the last year of 2013 yielded a total 25 articles for PubMed and 19 articles for SagePub. In the end, we compiled a total of 23 papers, 14 of which came from PubMed and nine of which came from SagePub. We included sixresearch that met the criteria.Conclusion: Existing research indicates that Intense Pulsed Light (IPL) therapy has the potential to alleviate the symptoms and manifestations of Dry Eye Disease (DED). Previous research did not demonstrate any significant adverse effects.